Comparable between rapid one step immunochromatographic assay and ELISA in the detection of prostate specific antigen in vaginal specimens of raped women - Vichan Peonim (2018)
Background: Rape is a crime found in Thailand nowadays. The crime is often lacking of eyewitnesses. Therefore, examination for forensic biological evidence becomes quite important, especially investigating sperm and semen in vaginal specimens of the victim. Acid phosphatase test for semen is commonly used in Thailand but is just a presumptive test. Recently, confirmatory kit tests became available in Thailand for detecting the prostate specific antigen (PSA) from semen. This test is simpler and cheaper than ELISA. Objective: To compare the rapid one-step immunochromatographic assay with ELISA for the detection of prostate specific antigen in vaginal specimens of raped women. Material and Method: A diagnostic test was conducted on the vaginal specimens of raped women that were sent to the laboratory of the Pathology Department, Faculty of Medicine, Ramathibodi Hospital, Mahidol University during April-August 2006. One hundred vaginal specimens were examined for prostate specific antigen by rapid one step immunochromatographic assay and compared with ELISA. Results: There were 85% and 83% of sensitivity, 85% and 85% of specificity, 85% and 85% of accuracy, 89% and 89% of positive predictive value, and 79% and 77% of negative predictive value from rapid one-step test kit and ELISA respectively. Conclusion: The result showed that there was no difference on specificity, accuracy and positive predictive value between the two methods but sensitivity and negative predictive value of rapid one-step test kit was better than ELISA. The research team recommends that rapid one-step test kit for prostate specific antigen should be routine service in vaginal specimens of raped women.